2002
DOI: 10.1177/107110070202300208
|View full text |Cite
|
Sign up to set email alerts
|

Proprioception of the Ankle: A Comparison Between Female Teenaged Gymnasts and Controls

Abstract: Proprioceptive mechanisms appear to play a role in stabilizing the joints and may serve as a means for interplay between static stabilizers and dynamic muscular restraints. The purpose of our study was to investigate whether or not gymnastic training has any effect on the balance and on proprioception in an ankle, as seen in gymnasts and in nongymnasts. We evaluated the proprioceptive ability of the ankle using four different tests (a one-leg-standing test, a single-limb-hopping test, an active angle-reproduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 21 publications
2
54
0
8
Order By: Relevance
“…This result is in agreement with past experiments demonstrating that gymnastic and strength training have a positive influence on both the sense of knee 19 and ankle 1,28 positions. Therefore, the ankle evertors weakness demonstrated by the individuals with FAI in the present study might have influenced negatively the ankle proprioception for some individuals with FAI.…”
Section: Characteristics Of the Individuals Withsupporting
confidence: 83%
“…This result is in agreement with past experiments demonstrating that gymnastic and strength training have a positive influence on both the sense of knee 19 and ankle 1,28 positions. Therefore, the ankle evertors weakness demonstrated by the individuals with FAI in the present study might have influenced negatively the ankle proprioception for some individuals with FAI.…”
Section: Characteristics Of the Individuals Withsupporting
confidence: 83%
“…The balance ability of gymnasts has mostly been compared to active control subjects [4,9,15,[21][22][23][24] , while two studies have compared them to other specific athletes. [13,15] Majority of studies reported some differences in balance ability; the one study that didn't [21] had the smallest sample size and might have been underpowered to detect statistical differences.…”
Section: Balance Ability Of Gymnasts Compared To Othersmentioning
confidence: 99%
“…Overall, it was found that gymnasts were equal to or out-performed non-gymnasts. When the balance test duration exceeded 20s, gymnasts did better than non-gymnasts [4,9,15,[22][23][24] but not when the test was 20s or less. [13,21] This result is a little surprising considering that gymnasts don't maintain static postures for much more than 2s during their routines.…”
Section: Balance Ability Of Gymnasts Compared To Othersmentioning
confidence: 99%
“…The greatest effect of the magnetic field therapy was observed in the ECDB test results for both the dominant and non-dominant legs. Maintaining this type of balance requires greater neural activity, and the results may reflect the effect of the magnetic field on the activation of the neural system, and proprioceptive and sensory inputs 3,4,14,15) . Thomas et al 16) showed significant improvements in normal standing balance and center of pressure, with eyes open or eyes closed, by a specific pulsed 200 μT magnetic field.…”
Section: Discussionmentioning
confidence: 99%